2021
DOI: 10.1016/j.jaac.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Elementary School Disciplinary Actions: Findings From the ABCD Study

Abstract: Objective: Detentions and suspensions are common practices of school discipline, despite evidence that they are largely ineffective and disproportionately affect children from racial and ethnic minority backgrounds, particularly Black children, and children of lower socioeconomic status. However, few studies have examined suspension and detention rates among race, ethnicity, and family structure (single parent versus secondary caregiver) when controlling for typical behaviors associated with detention and susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In addition to the ABCD study data [102], similar MDRs are shown in several national studies, such as the Fragile Families and Child Wellbeing Study (FFCWS) [69,[108][109][110][111], Population Assessment of Tobacco and Health (PATH) [47,[112][113][114], Education Longitudinal Study (ELS) [115], Monitoring the Future (MTF) [53], and National Survey of American Life (NSAL) [50], all showing weaker effects of SES indicators on outcomes for black children compared to white children. For example, in the PATH data, SES effects on future tobacco use [47], in the FFCWS study, SES effects on ADHD, impulsivity, obesity, and self-rated health [69,[108][109][110][111], in ELS, SES effects on school quality [115], and in MTF, SES effects on school performance were all weaker for black than white children [53]. In a longitudinal study of Flint, for MI adolescents, the effect of having married parents on subsequent anxiety symptoms was weaker for black than white children who were transitioning to young adulthood [116].…”
Section: Discussionsupporting
confidence: 53%
“…In addition to the ABCD study data [102], similar MDRs are shown in several national studies, such as the Fragile Families and Child Wellbeing Study (FFCWS) [69,[108][109][110][111], Population Assessment of Tobacco and Health (PATH) [47,[112][113][114], Education Longitudinal Study (ELS) [115], Monitoring the Future (MTF) [53], and National Survey of American Life (NSAL) [50], all showing weaker effects of SES indicators on outcomes for black children compared to white children. For example, in the PATH data, SES effects on future tobacco use [47], in the FFCWS study, SES effects on ADHD, impulsivity, obesity, and self-rated health [69,[108][109][110][111], in ELS, SES effects on school quality [115], and in MTF, SES effects on school performance were all weaker for black than white children [53]. In a longitudinal study of Flint, for MI adolescents, the effect of having married parents on subsequent anxiety symptoms was weaker for black than white children who were transitioning to young adulthood [116].…”
Section: Discussionsupporting
confidence: 53%
“…As such, we moved the item about being arrested to a new measure that asks more extensive questions about the role of police in a child’s community to assess this information in a broader cultural and environmental context. Further, it was noted that other items asked about youth being told they are being too rowdy, which may reflect differential experiences of Black youth rather than delinquency per se ( Fadus et al, 2020 ). The general review of measures related to delinquency and antisocial behavior also revealed concerns that this 10-item SRD measure needed to be modified and supplemented by items from other scales to more fully capture a broader range of delinquent behaviors in a more comprehensive and, potentially, less biased manner.…”
Section: Updates and Known Issues In The Demographic And Mental Health Assessments In The Abcd Studymentioning
confidence: 99%
“…The lack of racial diversity in medicine and cardiology is a culmination of inadequate resources in public schools in minority neighbourhoods, a dearth of Black, Hispanic, First Nation and Native American physicians to inspire minority children, the prohibitive costs of a college and medical education, and explicit and implicit biases by many "gatekeepers" from grade school to medical school. Race and sex biases that put women and minorities at a disadvantage for achieving a quality education have been well described and include biases going back to high school and earlier 83,84 . In a world where 70% of IAT test takers demonstrate an implicit association of White faces with "good" and Black faces with "bad 77 ", the minority child who dreams of being a physician faces nearly two decades of obstacles.…”
Section: Time To Intervene: Reducing the Impact Of Racism And Racial Bias In Cardiovascular Carementioning
confidence: 99%
“…Race and sex biases that put women and minorities at a disadvantage for achieving a quality education have been well described and include biases during the high school years and earlier. 82 , 83 . In a world where 70% of IAT takers demonstrate an implicit association of White faces with “good” and Black faces with “bad,” 76 the minority child who dreams of being a physician faces nearly 2 decades of obstacles.…”
Section: Time To Intervene: Reducing the Impact Of Racism And Racial Bias In Cardiovascular Carementioning
confidence: 99%